Evaluation of Aeromagnetic Data Over Some Parts of Lower Benue Trough, Nigeria Using Spectral Analysis - C. C Ezeh; O. S Okanya; A.O Usman; O. P Odoh (Journal La Multiapp, 2022)
We obtained, processed, and interpreted spectral analyses of aeromagnetic data across a portion of the Lower Benue Trough with the goal of estimating the depth to magnetic basement, modeling a conspicuous magnetic anomaly, identifying the basement topography, and evaluating basin configurations. Qualitative interpretation based on visual examination of the total magnetic intensive anomalies map, residual contour map, and first vertical derivative map reveals major faults trending east-west (E-W) and minor faults trending northeast-southwest (NE-SW), which is consistent with the structure of the lower Benue Trough. The western portion of the research region indicates structural change near the towns of Afikpo and Ishiagu, indicating areas of documented intrusive igneous body activity. According to the quantitative interpretation of the aeromagmatic data, the average sedimentary thickness is between (2.3 and 3.2 kilometers) and Quantitative interpretation utilizing spectral analysis identifies two distinct depth sources in the region: shallower sources ranging from 1.09 to 1.6 kilometers in the southern portion of the research area, and deeper sources ranging from 1.61 to 4.90 kilometers in the northern section. Additionally, the research reveals that the depths to the centroid and magnetic bodies (sedimentary thicknesses) vary between 5.02 and 10.65 kilometers and 0.23 and 3.5 kilometers, respectively. It was recommended that a ground magnetic survey be used in conjunction with this work to provide a more conclusive result.